Cerebral blood volume and oxygen supply uniformly increase following various intrathoracic pressure strains - Zhongxing Zhang (Nature Portfolio, 2017)
Abstract Intrathoracic pressure (ITP) swings challenge many physiological systems. The responses of cerebral hemodynamics to different ITP swings are still less well-known due to the complexity of cerebral circulation and methodological limitation. Using frequency-domain near-infrared spectroscopy and echocardiography, we measured changes in cerebral, muscular and cardiac hemodynamics in five graded respiratory maneuvers (RM), breath holding, moderate and strong Valsalva maneuvers (mVM/sVM) with 20 and 40 cmH2O increments in ITP, moderate and strong Mueller maneuvers (mMM/sMM) with 20 and 40 cmH2O decrements in ITP controlled by esophageal manometry. We found cerebral blood volume (CBV) maintains relative constant during the strains while it increases during the recoveries together with increased oxygen supply. By contrast changes in muscular blood volume (MBV) are mainly controlled by systemic changes. The graded changes of ITP during the maneuvers predict the changes of MBV but not CBV. Changes in left ventricular stroke volume and heart rate correlate to MBV but not to CBV. These results suggest the increased CBV after the ITP strains is brain specific, suggesting cerebral vasodilatation. Within the strains, cerebral oxygen saturation only decreases in sVM, indicating strong increment rather than decrement in ITP may be more challenging for the brain.